BDNF modulates intestinal barrier integrity through regulating the expression of tight junction proteins. Issue 3 (17th October 2016) - Yu, Y.‐B.; Zhao, D.‐Y.; Qi, Q.‐Q.; Long, X.; Li, X.; Chen, F.‐X.; Zuo, X.‐L.
Abstract: Background: Brain‐derived neurotrophic factor (BDNF) may play a vital role in the homeostatic regulation of intestinal barrier integrity. We aimed to investigate the physiological role of BDNF in maintaining the intestinal epithelial barrier using postinflammatory irritable bowel syndrome (PI‐IBS) mice and explore the underlying molecular mechanisms using intestinal epithelial cells in vitro. Methods: Postinflammatory‐IBS mice were induced by intrarectal administration of trinitrobenzene sulfonic acid and allowed to recover for 28 days. Frequency of defecation, fecal water content, colonic epithelial integrity and expressions of BDNF and tight junction (TJ) proteins (occludin, ZO‐1, claudin‐1, claudin‐2) of the PI‐IBS mice were investigated. Based on the results of animal studies, we further performed RT‐PCR and Western blots to assess how BDNF stimulation and BDNF knockdown impacted TJ proteins in the ht‐29 intestinal epithelial cells. Key Results: Water content of stools was significantly increased in the PI‐IBS mice compared with controls. Colonic mucosa from the PI‐IBS mice displayed epithelial barrier defects and exhibited increased protein expressions of BDNF and claudin‐2 and decreased protein expressions of occludin, ZO‐1 and claudin‐1. Furthermore, a siRNA against BDNF in the ht‐29 cells could effectively suppress BDNF gene and protein expressions, and subsequently reduce TJ gene and protein levels. When the ht‐29 cells were incubated with different doses of exogenous BDNF, significant increases of occludin, ZO‐1 and claudin‐1 and decreases of claudin‐2 protein were observed. Conclusions & Inferences: BDNF may play a role in regulating intestinal epithelial barrier via affecting the expression of TJ proteins. Abstract : Brain‐derived neurotrophic factor, a member of neurotrophins family, was originally known for its effects on the development and regeneration of central nervous system. In our study, we showed for the first time that BDNF may play a role in regulating intestinal epithelial barrier via affecting the expression of tight junction proteins.